A COMPARATIVE STUDY OF ACADEMIC PERFORMANCE OF STUDENTS ADMITTED THROUGH PRE-NCE & DIRECT ENTRY IN FINAL NCE EXAMINATION (A CASE STUDY OF ENGLISH DEPARTMENT FEDERAL COLLEGE OF EDUCATION, YOLA) - MICHIKA, AMINU AHMADU (Machakos University, 2019)
This research is designed to compare the academic performance of students admitted through the Pre-NCE and Direct entry in the NCE final Examination. The purpose of this research works was to ascertain whether the performance of PreNCE and Direct entry students in final NCE examination relate to their entry qualifications. A total of 314 students was used as population sample for the study out of 314 students, 150 are students admitted through PRE-NCE while 164 are those admitted through direct entry. A table format was designed to collect data concerning the already graduated students, the two-tailed z-test statistics was used to test the research hypothesis and the findings of the research revealed that students admitted through direct entry performed significantly higher than those admitted through the Pre-NCE in the final NCE Examination.
Keywords: Comparative analysis of academic performance of students at the final NCE examination.